Banking Responsibility for Employee Fault - Pedro, Alba; Nugroho, Krisna Wahyu; Napitupulu, Diana Ria Winanti (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This research discusses the legal responsibility of banks for mistakes made by employees in performing their duties, particularly in the context of the legal relationship between banks and customers. As a legal entity in the form of a Limited Liability Company, a bank has an obligation to maintain customer trust through the principles of prudence and consumer protection as regulated by the Banking Law and the Limited Liability Company Law.Purposes of the Research: This research aims to analyze the legal responsibility of banks for mistakes made by employees and explore to what extent a bank can be held accountable for negligence or abuse of authority by employees. The study also aims to explore the application of strict liability principles and their impact on the stability of the financial system and customer protection.Methods of the Research: This study uses a legal approach by analyzing relevant regulations, such as the Banking Law, the Limited Liability Company Law, and Article 1367 of the Civil Code regarding vicarious liability mechanisms. The study also explores the responsibility of the Board of Directors as the management of the bank.Findings of the Research: The research is expected to provide a clearer understanding of the legal responsibility mechanisms applied in the banking sector and their implications for managing the relationship between banks and customers, including the impact on customer protection and the supervision of the Board of Directors in preventing mistakes that harm customers.